Financial management decisions : principles and applications - Stewart, Alison; Gregory, Warwick; Lumby, Stephen; Hutchinson, Patrick (South Melbourne : Thomas Nelson, 1994)
This book is divided into two parts: Principles; Applications of Financial management decisions.
Keywords: Finance; Corporations; Corporations -- Finance; Finance -- Decision making